The power of character in the life of Imam Al-Bukhari: A Perspective in Positive Psychology - Zainal Badri, Khairul Nizam bin (Universitas Muhammadiyah Purwokerto, 2022)
The study of positive psychology was first introduced by the American psychologist Seligman in the early 2000s. Included in this study is the role of parents in instilling positive emotions and character strength to children. In addition to parents, teachers also play a role in developing positive psychological behaviors, especially in terms of motivation. This study focuses on the research of Imam Al-Bukhari, a great figure in the field of hadith in the context of whether the family and the education system in his time has had a great influence on his character and psychological behavior to succeed as a leading figure in the field of hadith. This qualitative pattern study successfully finds spiritual function, in triggering internal motivations that can be harnessed for the strengthening of positive character and emotions in the field of modern psychology.